Peranan Wanita Pendamping Suami Menjalankan Bisnis Keluarga Dalam Pengembangan Bisnis Studi Industri Kecil Kerupuk di Tuntang Kabupaten Semarang - Mahastanti, Linda Ariany; Nugrahanti, Yeterina Widi (Jurnal Siasat Bisnis, 2011)
The phenomenon of women working to fulfill their families’ needs in times of economic crisis is very interesting. This research focused on women co-entrepreneur who cooperated with their husbands in running their business. This research has been undertaken in Tuntang Semarang. The method of collecting data utilized descriptive statistic with questionnaire and in-depth interview with key persons. Findings examined whereas women co-entrepreneurs have barrier to operate their business like season, raw materials, financial capital and managerial, they have motivation to work due to improving their family prosperity. Keywords: women co-entrepreneur, motivasi, peran, hambatan, tuntang